Impact of musical rhythm on blood, physiological and welfare parameters in stabled horses - Oliveira, Fernanda Yumi Ueno de; Odakura, Agnês Markiy; de Castro Burbarelli, Maria Fernanda; Ouros, Caio César dos; de Lima Almeida Paz, Ibiara Correia [UNESP]; Braz, Jaqueline Murbach; Garcia, Rodrigo Garófallo; Caldara, Fabiana Ribeiro (Springer Nature, 2024)
The aim of this study was to evaluate the effects of two styles of classical music, based on different tempos (BPM), on the physiological and blood parameters of horses during social isolation and restriction of movements. First experiment was carried out using nine horses of no defined breed, distributed in Control, Slow-tempo music and Moderate-tempo music.For social isolation and restriction of movement, the animals were housed daily in individual stalls for two hours and exposed to the stimuli for 60 min, and eye temperature, heart rate, and respiratory rate were assessed. The second experiment was carried out using ten horses of no defined breed, distributed in a randomized design in treatments: Slow-tempo Music and Moderate-tempo Music. Blood samples were taken at the start and end of the experimental period to assess hematological and biochemical parameters and serum serotonin levels. Horses exposed to moderate-tempo music showed an increase in serum calcium levels, mean corpuscular hemoglobin (MCH), and total hemoglobin concentration, as well as a reduction in lymphocytes. Both types of music led to a significant increase in serotonin levels after one week of stimulation. Both musical rhythms are appropriate for promoting the well-being and health of stabled horses.
Keywords: Environmental enrichment; Equine; Eye temperature; Heart rate; Infrared thermography; Well-being